INFLUENCE OF ARTIFICIAL INTELLIGENCE ON UNDERGRADUATES' READING HABIT - Anyanwu, B.J.C.; Ejiogu, Paul Chibueze; Ibekwe, Chinedu; Onuoha, Noel Ikenna (African Journal of Social and Behavioural Sciences, 2025)
Artificial intelligence's role in education has evolved rapidly over the past few decades. This study sought to ascertain the influence of artificial intelligence on the reading habits of undergraduates of Imo State University, Owerri. The objectives of the study were to; ascertain the awareness level of undergraduates of Imo State University, Owerri towards AI, determine the knowledge level of undergraduates of Imo State University, Owerri towards AI, ascertain the influence of AI on the reading habits of undergraduates of Imo State University, Owerri, and find out other factors that can influence the reading habits of undergraduates of Imo State University, Owerri. The study was anchored on the technology determinism theory. This study employed a survey research design, with an estimated population of 21,000 participants. To determine the appropriate sample size, the Australian sample size calculator was utilized, resulting in a calculated sample size of 378 individuals. Furthermore, a multistage sampling technique was implemented to facilitate the selection process. The primary instrument utilized for data collection was a questionnaire, which was meticulously crafted using a four-point Likert scale. Findings of this study revealed that undergraduates of Imo State University are to a high extent aware of artificial intelligence, undergraduates of Imo State University, Owerri are highly knowledgeable towards artificial intelligence and its operations, artificial intelligence influences the reading habit of undergraduates of Imo State University Owerri, and there are other factors that influence reading habits of the respondents. The researcher recommended that undergraduates of Imo State University should expose themselves to more technological innovations as a means of aiding them in their academics, they should improve their knowledge on artificial intelligence and it operations, undergraduates of Imo State University, Owerri should reduce the usage of artificial intelligence in a bid to reduce it influence in their reading habit, and undergraduates of Imo State University, Owerri should adopt strategies to mitigate AI’s negative impact on reading habits.